Differential contributions of hippocampus and medial prefrontal cortex to self-projection and self-referential processing. (July 2015) - Kurczek, Jake; Wechsler, Emily; Ahuja, Shreya; Jensen, Unni; Cohen, Neal J.; Tranel, Daniel; Duff, Melissa
Abstract: Converging evidence points to a neural network that supports a range of abilities including remembering the past, thinking about the future, and introspecting about oneself and others. Neuroimaging studies find hippocampal activation during event construction tasks, and patients with hippocampal amnesia are impaired in their ability to (re)construct events of the past and the future. Neuroimaging studies of constructed experiences similarly implicate the medial prefrontal cortex (mPFC), but it remains unknown whether the mPFC is critical for such processes. The current study compares performance of five patients with bilateral mPFC damage, six patients with bilateral hippocampal damage, and demographically matched comparison participants on an event construction task. Participants were given a neutral cue word and asked to (re)construct events across four time conditions: real past, imagined past, imagined present, and future. These event narratives were analyzed for the number of internal and external details to quantify the extent of episodic (re)experiencing. Given the literature on the involvement of the mPFC in self-referential processing, we also analyzed the event narratives for self-references. The patients with mPFC damage did not differ from healthy comparison participants in their ability to construct highly detailed episodic events across time periods but displayed disruptions in their incorporation of the self. Patients with hippocampal damage showed the opposite pattern; they were impaired in their ability to construct highly detailed episodic events across time periods but not in their incorporation of the self. The results suggest differential contributions of hippocampus and medial prefrontal cortex to the distributed neural network for various forms of self-projection. Highlights: We examined the role of the MTL and mPFC in self-projection and self-referential processing. MTL patients were impaired in self-projection but not self-referential processing. mPFC patients were impaired in self-referential processing but not self-projection. MTL and mPFC make differential contributions to the neural network supporting self-projection and self-referential processing.